Management of Hypertaurodontism: An Endodontic Challenge - Saritha Vallabhaneni; Ganesh R More; Radhakrishna Gogineni (Wolters Kluwer Medknow Publications, 2011)
Taurodontism is a morpho-anatomical developmental anomaly rarely seen in teeth and usually found in association with other anomalies or as a part of syndrome. It is characterised by lack of constriction at the level of cementoenamel junction with elongated pulp chambers and apical displacement of bifurcation or trifurcation of roots. This gives the tooth a rectangular or cylindrical appearance. Endodontic treatment of a taurodont tooth is challenging, because it requires special care in handling and identifying the number of root canals. A case of endodontic treatment of a maxillary first molar with hypertaurodontism not associated with any syndrome is presented.